2021
DOI: 10.1007/s12325-021-01852-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Event Rates After Myocardial Infarction or Ischaemic Stroke in Patients with Additional Risk Factors: A Retrospective Population-Based Cohort Study

Abstract: Introduction: The impact of additional risk factors on major cardiovascular event (MACE) rates in patients with a history of myocardial infarction (MI) or ischaemic stroke (IS) treated with statins is not well defined. Methods: In this retrospective populationbased cohort study, patients with a history of MI or IS treated with moderate-or high-intensity statins were identified using Swedish national register data. Patients were incident (index event between July 2006 and December 2014 and followed from diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The event rate we estimated (14.3 events per 100 patient‐years) was similar in magnitude to a number of previous studies, 18 , 19 , 20 , 21 and lower than the event rate observed by Sciattella et al 22 (from 18.1 to 17.2 per 100 patient‐years) for patients with the acute coronary syndrome, IS, or PAD. However, in our study, we did not have data on the causes of deaths; thus, instead of CV death, all‐cause death was utilized as a composite in the CV events.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The event rate we estimated (14.3 events per 100 patient‐years) was similar in magnitude to a number of previous studies, 18 , 19 , 20 , 21 and lower than the event rate observed by Sciattella et al 22 (from 18.1 to 17.2 per 100 patient‐years) for patients with the acute coronary syndrome, IS, or PAD. However, in our study, we did not have data on the causes of deaths; thus, instead of CV death, all‐cause death was utilized as a composite in the CV events.…”
Section: Discussionsupporting
confidence: 87%
“…Diabetes and hypertension were the most important treatable predictors of recurrent events or death. Similarly, a previous registry study reported that additional CV risk factors elevated major CV event rates after MI or IS 1.5–3 times higher than in the overall MI and IS populations 18 . In a previous study, older age, prior stroke/TIA, prior atrial fibrillation, and elevated diastolic blood pressure at baseline were more likely associated with stroke than MI as the first event.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations